1994
DOI: 10.1007/bf00195908
|View full text |Cite
|
Sign up to set email alerts
|

The saluretic effect of the thiazide diuretic bemetizide in relation to the glomerular filtration rate

Abstract: The effect of the thiazide diuretic, bemetizide, on the excretion of Na+, K+, Cl-, Ca2+, and Mg2+ in relation to the glomerular filtration rate (GFR) was studied in 17 subjects whose creatinine clearances ranged from 133 to 5 ml.min-1. After a 2-day fluid and salt balanced control period, 25 mg bemetizide given orally induced natriuresis and kaliuresis which lasted for 24 h and were proportional to the GFR of the patients. The ratio of bemetizide-induced K+/Na+ excretion was always 0.17 irrespective of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…The same findings were reported earlier for other thiazides such as xipamide (KNAUF and MUTSCHLER 1984) and bemetizide (KNAUF et al 1994) studied in advanced renal failure. Obviously, nephron adaptation in renal failure maintains the ion transport characteristics of the early distal tubule, the site of action of thiazides.…”
Section: Responses In Renal Failuresupporting
confidence: 88%
See 2 more Smart Citations
“…The same findings were reported earlier for other thiazides such as xipamide (KNAUF and MUTSCHLER 1984) and bemetizide (KNAUF et al 1994) studied in advanced renal failure. Obviously, nephron adaptation in renal failure maintains the ion transport characteristics of the early distal tubule, the site of action of thiazides.…”
Section: Responses In Renal Failuresupporting
confidence: 88%
“…These diseases appear to have as a hallmark of their clinical syndrome disturbances of volume regulation. The effectiveness of acetazolamide co administered with thiazides corroborates increased proximal-tubular Na+ reabsorption as the major alteration in such disease states (KNAUF and MUTSCHLER 1994). The kidney responds to vascular underfilling by proximal tubular hyperreabsorption followed by a reduced Na+ load delivered to the loop of Henle and the distal tubule, the sites of diuretic action.…”
Section: Coadministration With Other Diuretics In Edematous Statementioning
confidence: 71%
See 1 more Smart Citation
“…Conversely, thiazides such as hydrochlorothiazide (HCTZ) are rarely used in patients with CKD because they can increase sodium fractional excretion by only 5% to 10% 7 . Some authors believe thiazides lose their effectiveness as soon as the GFR ranges below 30 mL/min, 8,9 and this notion has been widely accepted, but we and other authors have demonstrated in short‐term and experimental studies that the natriuretic effect of thiazides is preserved in patients with low GFR 10–14 …”
mentioning
confidence: 96%
“…Correlation between the excretion of sodium and potassium induced by oral hydrochlorothiazide, 25 mg, and the glomerular filtration rate. vanced renal failure, the maximal fractional excretion of sodium achieved by loop diuret ics was 25% [4] and that with the addition of a thiazide [3] was 15%. The FENa could be dou bled by the addition of amiloride [4,5].…”
Section: Qualitative Differences Of Responses To Diuretics In Renal Fmentioning
confidence: 99%